2003
DOI: 10.1074/jbc.m305072200
|View full text |Cite
|
Sign up to set email alerts
|

The Gap Junction-independent Tumor-suppressing Effect of Connexin 43

Abstract: The gap junction gene connexin 43 (Cx43) showed tumor-suppressing effects on various tumor cell lines. We have previously demonstrated that Cx43 inhibited expression of S phase kinase-associated protein 2 (Skp2), the human F-box protein that regulates the ubiquitination of p27. Cx43 did not alter the mRNA level of SKP2, but it promoted the degradation of the Skp2 proteins (Zhang, Y. W., Nakayama, K., Nakayama K. I., and Morita, I. (2003) Cancer Res. 63, 1623-1630). In this study, we showed that the specific ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
128
1
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 29 publications
7
128
1
7
Order By: Relevance
“…A down-regulation of cyclin D1 upon Cx43 transfection was revealed in human breast tumour cells [28] and in normal cell lines [29]. A similar correlation was observed for E9 mouse lung carcinoma and osteosarcoma cells [30].…”
Section: The Involvement Of Gap Junctions In the Regulation Of Tumoursupporting
confidence: 59%
See 2 more Smart Citations
“…A down-regulation of cyclin D1 upon Cx43 transfection was revealed in human breast tumour cells [28] and in normal cell lines [29]. A similar correlation was observed for E9 mouse lung carcinoma and osteosarcoma cells [30].…”
Section: The Involvement Of Gap Junctions In the Regulation Of Tumoursupporting
confidence: 59%
“…A down-regulation of cyclin D1 upon Cx43 transfection was revealed in human breast tumour cells [28] and in normal cell lines [29]. A similar correlation was observed for E9 mouse lung carcinoma and osteosarcoma cells [30]. Mechanistic studies demonstrated that the exogenous expression of Cx43 might exert its inhibitory effect on cell proliferation via the inhibition of the expression of S phase kinase-associated protein 2 (skp2), the protein that promotes the ubiquitination of cyclin-dependent kinase inhibitor p27kip.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…without enhancing GJIC (20). One is therefore driven to search for other mechanisms by which connexins may alter growth.…”
Section: Figmentioning
confidence: 99%
“…Recently, several reports have described that Cx43 plays a role in suppressing tumor growth independent of gap junction formation (19 -22). The C-terminal domain of Cx43 seems to be important in this tumor-inhibiting effect (20). Cx43 may also regulate the cell cycle by acting on the S-phase kinaseassociated protein (21).…”
mentioning
confidence: 99%